Remote Intraoperative Neural Response Telemetry: Technique and Results in Cochlear Implant Surgery. Issue 6 (July 2022) - Kouhi, Ali; Swanson, Austin; Fitzgerald, Matthew B.; Blevins, Nikolas H.
Abstract : Objective: Present results with remote intraoperative neural response telemetry (NRT) during cochlear implantation (CI) and its usefulness in overcoming the inefficiency of in person NRT. Study Design: Case series. Setting: Tertiary academic otology practice. Patients: All patients undergoing primary or revision CI, both adult and pediatric, were enrolled. Interventions: Remote intraoperative NRT performed by audiologists using a desktop computer to control a laptop in the operating room. Testing was performed over the hospital network using commercially available software. A single system was used to test all three FDA-approved manufacturers' devices. Main Outcome Measures: Success rate and time savings of remote NRT. Results: Out of 254 procedures, 252 (99.2%) underwent successful remote NRT. In two procedures (0.7%), remote testing was unsuccessful, and required in-person testing to address technical issues. Both failed attempts were due to hardware failure (OR laptop or headpiece problems). There was no relation between success of the procedure and patient/surgical factors such as difficult anatomy, or the approach used for inner ear access. The audiologist time saved using this approach was considerable when compared with in-person testing. Conclusions: Remote intraoperative NRT testing during cochlear implantation can be performed effectively using standard hardware and remote-control software. Especially important during the Covid-19 pandemic, such a procedure can reduce in-person contacts, and limit the number of individuals in the operating room. Remote testing can provide additional flexibility and efficiency in audiologist schedules.